Urgensi Mutu pada Lembaga Pendidikan - Syam Hadi Sy (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
Many educational institutions understand the scope of the quality of education; however, the implementation is still not optimal, even the quality of education is not considered important and useful for improving an educational institution. Therefore, the aim of this research is to provide views and concepts to managers of educational institutions so that they can think and be able to apply the quality of education properly so that the achievement of the vision and mission is effective. The method used is a literature review by examining scientific studies and research related to the quality of education. So that this research can be concluded that 1) The quality of education is a level of standardization that become a benchmark for managing educational institutions so that the goals can be achieved effectively and able to be a bridge to the success of educational institutions. 2) The educational quality instruments that must be met by educational institutions are to prioritize more transparent processes and professional both regarding students, staff, and the provision of learning infrastructure that is a necessity in improving the institution education. 3) Quality problems in educational institutions are characterized by the teaching style of teachers that are still traditional and educational facilities are still not optimal, so it needs evaluation for improvements to support quality education and there must be periodic changes both in the process, the suitability of educators and learning tools as well as more adequate facilities and infrastructure.